Effect of different dates of transplanting on leaf curl of tomato - S.D. SOMWANSHI, M.V. SABLE, SUNITA J. MAGAR* and (Indian Phytopathology, 2016)
Leaf curl is considered to be one of the important diseases of tomato causing heavy losses up the tune of 27-40% thoughout the world including India. Considering economic importance of disease the present investigation on effect of different dates of transplanting on tomato leaf curl disease was undertaken at the College of Agriculture, Latur (MS), during Rabi 2014. The results obtained in respect of effect of transplanting dates on disease incidence, whitefly population and fruit yield indicated that the crop sown on 15th Â October exhibits minimum disease incidence (58.34%) and whitefly population (1.01whitefly/plant) with fruit yield (6900kg/ha). While, maximum mean disease incidence (82.94%), whitefly population (1.13 whitefly/plant) and fruit yield (2611 kg/ha) was reported in the early sown crop (15thAugust).